PENGEMBANGAN GAME EDUKASI BERBASIS ANDROID SEBAGAI SUPLEMEN PEMBELAJARAN PADA MATERI PERBANDINGAN - Mokhamad Denta Ady Zakyanto; Atik Wintarti (MATHEdunesa, 2022)
The research goal is to produce a mathematics educational game called "Maze Math" as an android-based learning supplement on direct proportions and inverse proportion material as a valid, practical, and effective learning media. The development model in this study is the ADDIE model which includes Analysis, Design, Development, Implementation, and Evaluation. The instrument of validity are media and material expert validation questionnaire, practical instrument is a questionnaire of the use of educational games, and effectiveness instrument consist of a pretest and posttest. The educational game “Maze Math” was tested on 12 students of MTsN 1 Gresik with high, medium, and low math competency. This educational game has valid criteria because the results from the media expert and material expert validation questionnaire show percentage value of 82.71% (81%-90%). Maze Math is practical because the results from the practicality questionnaire filled out by students obtained 85.256% (85%-100%). The results of this study are also effective because the average N-gain categorized as high with a value of 0.740278 (> 0.7).